Histological evidence and clinical Correlations of renal TB-IRIS in HIV-positive patients and outcomes - Kahn, Thania (Department of Medicine, 2019)
Background Tuberculosis immune reconstitution inflammatory syndrome [TBCIRIS] is a well described clinical entity in HIV-infected patients that can affect multiple organs. There is however a paucity of information regarding renal involvement. This study aimed to illustrate the clinical, biochemical and histopathological features of HIV patients with suspected renal TBCIRIS, and to assess the mortality and renal outcomes of these patients. Methods The study was an observational, retrospective review of two established HIV positive renal biopsy registries [Groote Schuur Hospital and Livingstone Hospital Port Elizabeth, Eastern Cape].Renal biopsies were reviewed for the presence of granulomatous interstitial nephritis [GIN]. Patients’ folders and laboratory records were reviewed for evidence of tuberculosis [TB] and TBCIRIS. They were also reviewed for other causes of GIN i.e. drugs, fungal infection, sarcoidosis and infection. The study was approved by the UCT research ethics committee. The data was then analysed comparing 3 groups: [TB: no IRIS] (all TB cases with no features of IRIS), [TB + IRIS] (all cases with features of TBCIRIS) and [Other] (other causes of GIN). Results 68 HIV-positive renal biopsies were identified with GIN. The mean age was 37.5±9.1 years. There were 33 males (48.5%); 61 (89.7%) were of African black ethnicity, and there were no Caucasians in the study. 29 patients (43%) were noted to be on other medications known to cause GIN. The mean time from ART initiation to biopsy was 12 weeks, with the shorter average time being in the [TB + IRIS] group (6 weeks). The mean CD4 at biopsy was 105cells/µL, with the lowest CD4 seen in the in the [TB + IRIS] group (81cells/µL) (PC value 0.0175). The granulomas in the [TB + IRIS] group were noted to be more well-formed, with the highest number of poorly formed granulomas found in the [TB: no IRIS] group (25%) Sixteen (25%) of subjects had died within 2 years of their biopsy, with the majority of deaths occurring in the [TB : no IRIS] group (12/48, 44%), (PCvalue!0.01). Conclusion This study is the largest series of renal TBCIRIS that adds to the very limited case reports in the literature. There is a clinical entity of TB renal CIRIS that is associated with GIN on renal biopsy. Significant findings were those of a shorter time from ART initiation to biopsy in the [TB + IRIS] group, a lower CD4 count at biopsy and nadir in the [TB + IRIS] group with more well-formed granulomas. The majority of deaths within 2 years were noted in the [TB: no IRIS] group. This entity seems to be in keeping with other TBC IRIS descriptions previously published.